GOVERNMENT SPENDING AND REGIONAL ECONOMIC GROWTH: THE MEDIATING EFFECT OF HUMAN DEVELOPMENT INDEX - Sasongko, Handaru Edit; Wibowo, Puji (Fakultas Ekonomi dan Bisnis, UNTAN, 2022)
The dynamic of local government spending on education, health care, and infrastructure in the region shows an interesting phenomenon in the last decade. Despite the fact that budget expenditures of sub national governments have grown substantially, the pace of the human development index and the rate of economic growth have provided us different pictures. This study aims to analyze the impact of the three spending groups on the quality of human development and economic growth in Indonesia. This research used purposive sampling method to obtain data from as many as 464 districts/cities that were observed during the 2016-2018 period. Based on panel analysis, there was evidence that health spending had a positive effect on the human development index and community welfare. By contrast, spending on education and infrastructure did not have a good effect on these two development indicators. Based on the Sobel test, only health spending had a positive indirect effect on economic growth through the quality of human development. Meanwhile, education spending did not have a significant effect on economic growth, either directly or indirectly. Future research may develop another measurement for insfrastructure spending to provide better proxy.